2017
DOI: 10.1002/2016gc006696
|View full text |Cite
|
Sign up to set email alerts
|

Origin of geochemical mantle components: Role of spreading ridges and thermal evolution of mantle

Abstract: We explore the element redistribution at mid-ocean ridges (MOR) using a numerical model to evaluate the role of decompression melting of the mantle in Earth's geochemical cycle, with focus on the formation of the depleted mantle component. Our model uses a trace element mass balance based on an internally consistent thermodynamic-petrologic computation to explain the composition of MOR basalt (MORB) and residual peridotite. Model results for MORB-like basalts from 3.5 to 0 Ga indicate a high mantle potential t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 194 publications
(493 reference statements)
0
8
0
Order By: Relevance
“… *Average δ 82 Se (±95% CI, N = 27) and Sr-Nd isotopic ratios (±95% CI, N = 66) of PAR glasses [( 21 , 46 ) and references therein]; δ 34 S (±1 s ) from ( 46 ). †δ 82 Se (±95% CI, N = 31) is estimated using all the depleted MORBs from the MAR and PAR; δ 34 S (±1 s ) and Sr-Nd isotopic ratios from ( 15 , 27 , 48 ). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… *Average δ 82 Se (±95% CI, N = 27) and Sr-Nd isotopic ratios (±95% CI, N = 66) of PAR glasses [( 21 , 46 ) and references therein]; δ 34 S (±1 s ) from ( 46 ). †δ 82 Se (±95% CI, N = 31) is estimated using all the depleted MORBs from the MAR and PAR; δ 34 S (±1 s ) and Sr-Nd isotopic ratios from ( 15 , 27 , 48 ). …”
Section: Resultsmentioning
confidence: 99%
“…See the Supplementary Materials and Methods for the sample literature data. † 82 Se (±95% CI, N = 31) is estimated using all the depleted MORBs from the MAR and PAR;  34 S (±1s) and Sr-Nd isotopic ratios from(15,27,48).…”
mentioning
confidence: 99%
“…Primitive mantle‐normalized trace‐element patterns for modelled clinopyroxene (grey lines) and the Muslim Bagh basal lherzolite (AM‐33 and B‐6). The influx composition (black line) in the influx‐induced open‐system melting models (b, c) was the composition of a slab‐derived fluid composition estimated from Japanese arc magma (Kimura, Gill, van Keken, Kawabata, & Skora, 2017). Details of the model were given in the text.…”
Section: Discussionmentioning
confidence: 99%
“…The primitive mantle values are from McDonough and Sun (1995). The influx composition in the influx‐induced open‐system melting models (not shown in this diagram) was the composition of a slab‐derived fluid estimated from Japanese arc magma (Kimura et al, 2017)…”
Section: Discussionmentioning
confidence: 99%
“…Stracke et al (2005) subsequently modified the definition of FOZO to a range of 206 Pb/ 204 Pb compositions that includes but extends beyond the high 206 Pb/ 204 Pb end of the MORB array. More recent studies have proposed the existence of a deep reservoir of intermediate isotopic composition, formed early in Earth's history, called the early depleted reservoir (EDR), situated near PREMA (Boyet & Carlson, 2005, 2006Jackson et al, 2010;Kimura et al, 2017). Although recent studies using the short-lived 146 Sm-142 Nd radiometric system have obviated the need for EDR (Bouvier & Boyet, 2016;Burkhardt et al, 2016), others using geochemical models or the short-lived 182 Hf-182 W radiometric system have suggested that such a reservoir is preserved in the mantle (Kimura et al, 2017;Rizo et al, 2016).…”
Section: 1029/2019gc008336mentioning
confidence: 99%